ELEMEN-ELEMEN PSIKOLOGI DALAM ALQURAN STUDI TENTANG NAFS, ‘AQL, QALB, RUH, DAN FITRAH - Napitupulu, Dedi Sahputra (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2019)
This paper describes the elements in the Noble Qur'an, psychology term that will be scrutinized is the nafs ' aql, qalb, ruh and fitrah. By using the library study results showed that nafs was the side that shows human beings concerning the potential good and bad. While 'aql is a power to acquire knowledge therefore has the power to make sense of abstract objects that captured the five senses. As for the definition of a substance is the qalb smooth functioning and getting to know the nature of things as well as have the ability to reflect. Ruh make man has servant of God purity. Tend to things eternal, peace and quiet. Fitrah is innate for religious and believe in God, with an innate human potential has been given more to believe in God, but over time people became disobedient to God because the environment shape it. The fifth element of psychology to be able to walk properly and is functioning to its fullest potential according to their respective wants always always cleaned and maintained from various forms of disobedience. This concept is the one who makes the difference between Islamic psychology with conventional psychology.